HCV treatment rates and sustained viral response among people who inject drugs in seven UK sites: real world results and modelling of treatment impact. Issue 4 (7th October 2014) - Martin, N. K.; Foster, G. R.; Vilar, J.; Ryder, S.; E. Cramp, M.; Gordon, F.; Dillon, J. F.; Craine, N.; Busse, H.; Clements, A.; Hutchinson, S. J.; Ustianowski, A.; et al.
Summary Hepatitis C virus (HCV) antiviral treatment for people who inject drugs (PWID) could prevent onwards transmission and reduce chronic prevalence. We assessed current PWID treatment rates in seven UK settings and projected the potential impact of current and scaled‐up treatment on HCV chronic prevalence. Data on number of PWID treated and sustained viral response rates (SVR) were collected from seven UK settings: Bristol (37–48% HCV chronic prevalence among PWID), East London (37–48%), Manchester (48–56%), Nottingham (37–44%), Plymouth (30–37%), Dundee (20–27%) and North Wales (27–33%). A model of HCV transmission among PWID projected the 10‐year impact of (i) current treatment rates and SVR (ii) scale‐up with interferon‐free direct acting antivirals (IFN‐free DAAs) with 90% SVR. Treatment rates varied from <5 to over 25 per 1000 PWID. Pooled intention‐to‐treat SVR for PWID were 45% genotypes 1/4 [95%CI 33–57%] and 61% genotypes 2/3 [95%CI 47–76%]. Projections of chronic HCV prevalence among PWID after 10 years of current levels of treatment overlapped substantially with current HCV prevalence estimates. Scaling‐up treatment to 26/1000 PWID annually (achieved already in two sites) with IFN‐free DAAs could achieve an observable absolute reduction in HCV chronic prevalence of at least 15% among PWID in all sites and greater than a halving in chronic HCV in Plymouth, Dundee and North Wales within a decade. Current treatment rates among PWID are unlikely to achieve observable reductions in HCV chronic prevalence over the next 10 years. Achievable scale‐up, however, could lead to substantial reductions in HCV chronic prevalence.